Analisis Makna Konotasi Negatif Pada Iklan 'Permen Milkita' Pada Awal Tahun 2000-An - Sofi Ullanuha Cahyani; Tannia Alfianti Putri; Wawan Hermawan; Reisya Diva Maharani Putri; Ella Agustian Utami; Aditya Nata Widigda (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
Television advertising is a form of promotion of products, services or brands delivered via television channels. They are usually short videos shown between regular programs. The main purpose of advertising on television is to influence viewers to buy the product or use the service being advertised. Television advertising often uses a variety of marketing techniques, including narration, music, attractive visuals, and celebrities, to attract viewers' attention and increase the appeal of the product or service being promoted. Advertising is an inseparable part of television media. Human life today cannot be separated from the influence of television. Various information can be obtained quickly. To meet the entertainment needs of humans or television viewers, television always inserts advertising shows. Besides having commercial purposes, advertising also has information value contained in it. Advertisers, both private and government, try to introduce and encourage people to do what the advertisers hope for. Advertising via television has various advantages compared to other types of media which include wide reach, selectivity and flexibility, focus of attention, creativity and effect, prestige, and a certain time (Andrianto, 2018).